Gelandangan Kepung Kota Semarang, 1950-1964: Kedatangan, Kehidupan, dan Penanggulangan - Jumaidi, Susanto; Fatkhia, Feren Fatma (Historia Madania: Jurnal Ilmu Sejarah, 2024)
The This research examines the phenomenon of homelessness in Semarang throughout 1950-1964 with a problem formulation, (a) what is the process of the rise of homelessness in Semarang City? (b) how do homeless people survive amidst the tumultuous economy in Semarang?, (c) what are the government's efforts to solve this problem? The research method used is a historical research method consisting of heuristics, source criticism, interpretation and historiography. Primary sources used include contemporary newspapers such as Suara Merdeka in 1954th and 1964th, the locomotive 1950th and 1955th, the Preangerbode 1953th, democratic socialist daily newspaper in 1962th. Additionally This research is also supported by secondary sources in the form of previous study literature. The results of this research show that this phenomenon is caused by urbanization, economic competition and disasters. They live and live uncertainly. The government has tried to provide compensation, provide housing camps, including plans to transmigrate homeless people outside Java to solve this problem. Keywords: homeless, social, Semarang city.